Conselhos gestores e políticas públicas: notas preliminares de desafios teóricos e analíticos - Pires, Elson [UNESP]; Ávila, Heleni De; Nascimento, Jucileide (Cortez Editora Ltda, 2024)
This essay is the result of readings and studies about the relationships between public policies, local government, territories and Social Work. It is about rescuing the relationship between public policies, with management councils and the consequences they bring to the debate on territorial governance, which mobilizes the collective identity of subjects, observing their plurality in the arena of disputes for local power and resistance in in favor of institutional changes and social transformations.

O presente ensaio resulta de leituras e estudos acerca das relações entre as políticas públicas, o poder local, os territórios e o Serviço Social. Trata-se de resgatar a relação entre as políticas públicas, com os conselhos gestores, e as consequências que trazem ao debate da governança territorial, que mobiliza a identidade coletiva dos sujeitos, observando a pluralidade destes na arena de disputas pelo poder local e resistências em prol de mudanças institucionais e de transformações sociais.
Management councils and public policies: preliminar notes on theoretical and analytical challenges
Keywords: Management councils; Territorial governance; Public policy; Social Work; Territory; Conselhos gestores; Governança territorial; Políticas públicas; Serviço Social; Território